2002
DOI: 10.1046/j.1365-2036.2002.01292.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rabeprazole, 20 mg, or esomeprazole, 20 mg, on 24‐h intragastric pH and serum gastrin in healthy subjects

Abstract: SUMMARYAim: To compare the antisecretory effects of rabeprazole and esomeprazole in an open, randomized, two-way crossover, clinical pharmacology study. Methods: Twenty-four healthy subjects (14 men, 10 women; mean age 26.8 years) received rabeprazole 20 mg or esomeprazole 20 mg daily on days 1-5, with a 14-day Ôwash-outÕ. Intragastric pH was recorded continuously, and serum gastrin measured, on days 0, 1 and 5. Results: On day 0, mean intragastric pH AUC was significantly higher before the esomeprazole than b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
2
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 16 publications
5
49
2
2
Order By: Relevance
“…where rabeprazole was found to be a better antisecretory agent than esomeprazole. [20] In this study, improvement was seen in all five domains of QOLRAD scoring with both the drugs. But the improvement with rabeprazole was found to be more than esomeprazole over 1 month.…”
Section: Discussionmentioning
confidence: 53%
“…where rabeprazole was found to be a better antisecretory agent than esomeprazole. [20] In this study, improvement was seen in all five domains of QOLRAD scoring with both the drugs. But the improvement with rabeprazole was found to be more than esomeprazole over 1 month.…”
Section: Discussionmentioning
confidence: 53%
“…4 Rabeprazole has a greater capacity to increase gastrin levels than other proton pump inhibitors. 5,6 This might explain why, in the present case, the patient's panic symptoms disappeared after rabeprazole was switched to esomeprazole. The mechanism whereby high serum concentrations of rabeprazole induce psychotic disorder is unknown, however.…”
Section: Discussionmentioning
confidence: 65%
“…The outcome of these rather rigorous inclusion criteria and design was a difficulty in fulfilling our initial goal of recruiting a large cohort of patients. Finally, from a number of candidate PPIs, we chose rabeprazole, since this drug has a number of potential advantages: (a) a rapid onset of action as shown by gastric pH monitoring studies [3,12,13] ; (b) a good safety profile; (c) a lack of drug interactions due to its specificity in terms of hepatic and non-hepatic metabolic pathways [4,5] ; and (d) its effectiveness in the treatment of some symptoms associated with GERD [14] . The results of our study are consistent with other studies of PPI tests which have without exception demonstrated the high sensitivity and poor specificity of this diagnostic approach [1] .…”
Section: Discussionmentioning
confidence: 99%